Pengaruh Latihan Imagery dan Konsentrasi Terhadap Hasil Latihan Passing Sepakbola Pada Atlet di Sekolah Sepakbola Bintang Kalinegoro - Ilham, Ilham Jaya Kusuma Dwi Syahputra; Soedjatmiko, Soedjatmiko; setiawan, arif (Universitas Negeri Semarang, 2025)
Imagery training is rarely used by coaches to improve the quality of passing techniques in soccer. This study aims for soccer coaches or athletes to apply imagery training to achieve maximum performance.The research method in this study uses a quantitative approach with a quasi-experimental research method. The population in this study were all SSB Bintang Kalinegoro athletes totaling 60. The sample used was 24 athletes. Data collection used a grid concentration test and a passing test. Quantitative data analysis consisted of a normality test, a homogeneity test, and a hypothesis test.The results showed cognitive specific sig p of 0.001, motivational general mastery sig p of 0.010, high concentration sig p of 0.008, low concentration sig p of 0.001, the interaction of imagery and concentration on passing results obtained sig p of 0.001 which means that all of them have interactions.Conclusion: There is an influence of cognitive specific, motivational general mastery, high concentration, and low concentration training methods on the passing training results of Bintang Kalinegoro soccer school players. The Cognitive Specific training method is better applied to high concentration groups, while the Motivational general mastery training method is better applied to low concentration groups.